Sistem Pakar Diagnosa Penyakit Ginjal dengan menggunakan Algoritma Bayes - Khoironi; Abdul Rosyid; Muhammad Azmi (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2020)
Expert systems are computer-based systems that use knowledge, facts and reasoning techniques to solve problems that usually only an expert can solve in a particular field. Expert systems provide added value to technology to assist in an increasingly sophisticated information age. This expert system application produces output in the form of possible kidney disease based on the symptoms felt by the user. This system uses the Bayes method. The system will look for the highest probability value, from various possible types of disease based on the information requested by the user and exclude the user. The system for diagnosing kidney disease is determined by determining the type of disease based on the user's symptoms. The resulting Bayes value is between 0 and 1. If the resulting Bayes value is continuous, the higher the certainty that the disease is affected. In fact, if the resulting Bayes value is continuous, the less certain the disease involved is.